2007
DOI: 10.2190/cs.9.2.b
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Parenting Styles Experienced during Childhood, Anxiety, Motivation, and Academic Success in College Students

Abstract: The current study examined the relationships among parenting styles experienced in childhood, anxiety, motivation, and academic success in college students. Results suggested that fathers' authoritative parenting was related to decreases, whereas mothers' authoritarian parenting was related to increases, in college students' anxiety. Further, mothers' and fathers' authoritative parenting, mothers' authoritarian parenting, and college students' anxiety and motivation were related to college students' grade poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 32 publications
4
23
0
2
Order By: Relevance
“…Such a finding supported earlier works of Bean et al (2006), Milevsky et al (2006) and Silva et al (2007) where parenting was measured separately for each parent. However, studies conducted by Margolin et al (2001) and McHale et al (2002) demonstrated the need to conceptualise parenting as interdependent concept where relationship between mothers' and fathers' parenting practices were presented as an important contribution to children's functioning, perhaps more important than the individual contributions of mothers' or fathers' parenting styles.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Such a finding supported earlier works of Bean et al (2006), Milevsky et al (2006) and Silva et al (2007) where parenting was measured separately for each parent. However, studies conducted by Margolin et al (2001) and McHale et al (2002) demonstrated the need to conceptualise parenting as interdependent concept where relationship between mothers' and fathers' parenting practices were presented as an important contribution to children's functioning, perhaps more important than the individual contributions of mothers' or fathers' parenting styles.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, it is necessary to understand that both parents are equally important and have a role to play in supporting their children autonomy and self-reliance. The necessity to conceptualise parenting style from gender perspectives was as well suggested by Silva et al (2007) who was of opinion that students' cognitive skills could be improved with the interventions that address maternal and paternal parenting styles separately. However, in the study of Simons and Conger (2007), it was stated that researchers often examined the parenting of mothers and assumed that fathers' parenting is the same as mothers'.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as many as 92% of college students who are identified as mildly to moderately depressed may show evidence of academic impairment [3]. Similarly, a negative relationship exists between college students' experience of anxiety and their college grade point averages [21]. Thus, the connection between stress and emerging adults' adjustment, particularly for those who are pursuing college education, is apparent; however, those variables that may help to explain the relationship between stress and adjustment deserves attention.…”
Section: Emerging Adult Adjustmentmentioning
confidence: 99%
“…Isso explica, hipoteticamente, por que o uso de práticas idênticas, por famílias de estilos distintos, gera diferentes resultados nos comportamentos da criança e do adolescente (Darling e Steinberg, 1993). Apesar de pesquisas confi rmarem a relação entre os estilos, práticas e os comportamentos na infância e na adolescência (veja, por exemplo, Cuarati-Burgio, 2001;Silva et al, 2007), não foi encontrado nenhum estudo empírico, nos bancos PsycINFO e Web of Science -até o ano de 2009 -, que confi rme a dinâmica apresentada por Darling e Steinberg (1993).…”
Section: Estilos Parentaisunclassified
“…Essas investigações têm associado, por um lado, os estilos parentais a diversas características psicopatológicos, tais como transtornos alimentares e sobrepeso (Haslam et al, 2008;Rhee et al, 2006), uso de drogas (Castrucci e Gerlach, 2006;Choquet et al, 2008;Tucker et al, 2008), ansiedade e depressão (Choquet et al, 2008;Dwairy, 2004;Silva et al, 2007) e traços de personalidade desadaptados (Yu et al, 2007). Por outro lado, há estudos que apontam para relações entre os estilos e aspectos positivos do desenvolvimento, como resiliência e coping (Cuarati-Burgio, 2001; Nij hof e Engels, 2007), qualidade de vida (Zimmermann et al, 2008), alimentação saudável (Arredondo et al, 2006) e desempenho acadêmico (Boon, 2007;Spera, 2006).…”
Section: Estilos Parentaisunclassified